THE INFLUENCE OF MODIFIERS ON INCREASING THE DURABILITY OF ASPHALT CONCRETE PAVEMENTS (Eureka Journal of Civil, Architecture and Urban Studies, 2025)
This article shows the use of increasing the durability of modified asphalt concrete formed with the addition of polymers " Kraton D1186" and surface-forming additives SFM "SP-OEP" with long-term water saturation, which is influenced by the main parameters of asphalt concrete, concrete is also considered in terms of frost resistance, corrosion resistance and crack resistance.